Fortification of puffed biscuits with chitin and crayfish shell: Effect on physicochemical property and starch digestion - Bai, Chan; Zhu, Jiguo; Xiong, Guangquan; Wang, Wenqing; Wang, Juguang; Qiu, Liang; Zhang, Qingfang; Liao, Tao (Frontiers in Nutrition, 2023)
Chitin is a polysaccharide and possesses numerous beneficial properties such as nontoxicity, biodegradability and biocompatibility, which draws much attention to its applications in food. Crayfish shell is a source of chitin alongside an antioxidants and a potential source of beneficial dietary fiber. In this study, chitin (CH) and crayfish shell (CS) with different concentrations were used to study their impact on pasting characteristics of flour mixture (wheat flour and glutinous rice flour) and influence on physicochemical and starch digestion property of puffed biscuit. The Rapid Visco-Analyzer results showed that the viscosity of powder mixture was decreased with the ratio of CH and CS increased. CH resulted in lowest peak viscosity and breakdown values of mixed powder. It was indicated that increasing amounts of CH and CS led to significantly reduced moisture content, expansion ratio but raised density of biscuits. CH and CS inhibited starch digestion and promoted a remarkable increase (P＜0.05) of resistant starch (RS) content. The hydrolysis kinetic analysis suggested a decelerating influence of CH on the hydrolysis content with lower values of equilibrium hydrolysis percentage (C∞) while CS on hydrolysis rate with lower kinetic constant (K). The estimated glycemic index (eGI) of the CH (15-20%) samples were below 55. These results are of great significance in delaying starch digestion and provided a better choice in design of fried puffed snacks for special crowd with chronic diseases such as diabetes, cardiovascular disease, and obesity.